(untitled) (The Journal of Psychology and Sociology, 2013)
This article represents a generalized exposition analyzing peculiarities of the manifestation of facilitative ability in the field of education and upbringing. The most characteristic issues dealing with facilitative ability investigation in this field have been studied. They are a pedagogic system with a facilitation mechanism; the influence of facilitation display on an educational system in which it is manifested; characteristics of a teacher-facilitator; the use of facilitative ability in the different forms of an educational process; the importance of facilitation in the whole development of a student’s personality and formation of their separate features etc. A great prominence is given to the ways of further investigation of facilitative potential manifestation in the educational area.